Plasma Levels of Endothelial Cell-Specific Molecule-1 as a Potential Biomarker of Oral Cancer Progression - Yang, Wei-En (Int J Med Sci, 2017)
In Taiwan, oral cancer is the fourth most common cancer and the most common malignancy with a poor prognosis. Endothelial cell-specific molecule-1 (ESM-1) is secreted by vascular endothelial cells in the liver, lungs, kidneys, and gastrointestinal tract. ESM-1 expression is associated with tumor prognosis, metastasis, and angiogenesis in many cancers. However, few studies have examined the association of plasma ESM-1 levels with oral squamous cell carcinoma (OSCC) progression. We measured the plasma ESM-1 levels of 438 male OSCC patients through a commercial enzyme-linked immunosorbent assay. The Cancer Genome Atlas (TCGA) dataset was also used to analyze the ESM-1 levels in 328 OSCC patients and 33 normal tissues. Our results revealed that the plasma levels of ESM-1 in OSCC patients were significantly associated with the tumor (T) status but not with the lymph node status, metastasis, and cell differentiation. TCGA bioinformatics database analysis revealed that ESM-1 expression was significantly higher in OSCC patients than in normal individuals (p < 0.05). In addition, the examination revealed similar results for the ESM-1 expression levels and pathological stage in OSCC. In conclusion, plasma ESM-1 is a novel biomarker for predicting the T status in OSCC patients.